Pengaruh Latihan Plyometric Box Jump dan Roll Abs terhadap Jauh Start Jump dan Underwater Velocity pada Atlet Galaxy Aquatics (SPRINTER: Jurnal Ilmu Olahraga, 2026)
The start and underwater phases are primary determinants of success in the 50 m finswimming sprint. This study examined the effects of box jump and roll abs training on start jump distance and 15 m underwater velocity in Galaxy Aquatic athletes. A quasi experimental one group pretest–posttest design was used with 10 purposively selected athletes. The 8 week intervention comprised three sessions per week. Measurements included start jump distance and 15 m underwater time; data were analyzed with paired sample t tests. Results indicated a mean increase in jump distance of 7.2% (p = 0.000) and an improvement in underwater velocity of 6.1% (p = 0.003). Box jump training improved lower limb explosive power while roll abs enhanced core stability for maintaining streamline position. In conclusion, the combined program significantly improved early phase performance in finswimmers and is recommended for PORPROV preparation.